Minat Siswa Terhadap Pembelajaran Renang di SMA Negeri 5 Karawang: Student Interest in Learning Swimming - Dimas Prasetyo; Ruslan Abdul Gani; Bambang Ismaya (Jurnal Literasi Olahraga, 2021)
In this study, the problem raised was how the class students interest was X on swimming. The purpose of this study was to determine interest in sports swimming for Class X student of SMA Negeri 5 Karawang. The population in this study were students of Class X SMA Negeri 5 Karawang. With a total of 210 students, and the sampole used in this study was 210 students, namely the total sampling technique. The variable in this research is interest Class X student of SMA Negeri 5 Karawang. Against swimming this research using a survey method with data collection using a questionneire. The data analysis used in this research is percentage descriptive statistics. The results showed that the in Class X SMA Negeri 5 Karawang. 2 students or 2 students have very hogh interest in swimming 0.95%, as many as 98 students or 46.67% have high interest, as many as 87 students or 41.43% have low interest, and as many as 23 students or 10.95% have very low interest.based on the result of the study it was conluded that the interest og Class X SMA Negeri 5 Karawang. Basically has a high interest in swimming, namely it is proven that as many as 98 students or 46.67% high interest in swimming sports Class X student of SMA Negeri 5 Karawang.influenced by two things first actual motivation amounted to 58.54%, the second is the extrinsic motivation factor of 52.49%. from the results of this study are sugested to perents to provide motivation children and facilitate them to diligently participate in swimming in agar school can develop their talents, to students should be able to add insight through printed or electronoic media about swimming sports, to teachers in order toi maintain a fun way of teaching, because of this way of techinng proved to be liked by the students, while the school suggested that swimming sports are used as aextracurriculer activities so that they can spur interest as well directing students talents towards swimming.